Archive Management and Document Control As A Support For Mining Company Accounting Information Systems: Manajemen Arsip dan Pengendalian Dokumen Sebagai Pendukung Sistem Informasi Akuntansi Perusahaan Pertambangan - Victor Sitepu, Hans (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
The mining industry is a capital-intensive sector that grows year after year. Every company in this industry continually strives to maximize value for its owners. Every operation carried out by the organization is required to be effective and efficient in order to generate a lasting competitive advantage. Implementing a trustworthy and integrated accounting information system is an essential step in achieving this goal. By implementing this method, mining companies intend to promote the development of a strong and dependable performance and growth assessment. Archive management and document control are critical components of the system installation process. Archives management and document control are critical supports for the deployment of productive accounting and management information systems, which can decide a mining company's success in meeting its objectives. Not many mining businesses have robust, dependable, effective, and efficient archive management and document control processes, much alone good capabilities. That is why it is required to offer training sessions on Archive Management and Document Control for participants from two mining companies in Sumatra and Kalimantan. The mining industry is a strength of CV Bara Indo Consulting, the primary organizer of this activity, which partners with the author as a demonstration of the author's community commitment. This training activity was ultimately able to increase participants' conceptions, understanding, and skills in implementing archive management and document control functions in their firms. This is demonstrated by the participants' post-test results, all of which have exceeded the lower limit of graduation criteria.